Identification of Biomarkers of Mercury Contamination in Brachyplatystoma filamentosum of the Madeira River, Brazil, Using Metalloproteomic Strategies - de Queiroz, João Vitor [UNESP]; Vieira, José Cavalcante Souza [UNESP]; de Oliveira, Grasieli [UNESP]; Braga, Camila Pereira; da Cunha Bataglioli, Izabela [UNESP]; da Silva, Janaína Macedo [UNESP]; de Paula Araújo, Wellington Luiz [UNESP]; de Magalhães Padilha, Pedro [UNESP] (Springer Nature, 2018)
Predator fish can accumulate high levels of mercury, which qualifies them as potential indicators of this toxic metal. The predatory species Brachyplatystoma filamentosum, popularly known as filhote, is among the most consumed species in the Brazilian Amazon. Continuing the metalloproteomic studies of mercury in Amazonian fishes that have been developed in the last 5 years, the present paper provides the data of protein characterization associated with mercury in muscle and liver samples of filhote (Brachyplatystoma filamentosum) collected in the Madeira River, Brazilian Amazon. The mercury concentration in the muscle and liver samples was determined by graphite furnace atomic absorption spectrometry (GFAAS). The protein fraction was extracted in an aqueous medium, and later, a fractional precipitation procedure was performed to obtain the protein pellets. Then, the proteome of the tissue samples of this fish species was separated by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE), and a mercury mapping of the protein spots was carried out by GFAAS after acid digestion. Protein spots that had mercury were characterized by mass spectrometry with electrospray ionization in sequence (ESI-MS/MS) after tryptic digestion. It was possible to characterize 11 mercury-associated protein spots that presented biomarker characteristics and could be used to monitor mercury in fish species of the Amazon region. Thus, the metalloproteomic strategies used in the present study allowed us to characterize 11 mercury-associated protein spots. It should be noted that the protein spots identified as GFRP, TMEM186, TMEM57B, and BHMT, which have coordination sites for elements with characteristics of soft acids, such as mercury, can be used as biomarkers of mercury contamination in monitoring studies of this toxic metal in fish species from the Amazon region.
Keywords: Biomarkers; Mercury; Proteins; Proteomics; System biology